THE USE OF COOKING VIDEO TO IMPROVE STUDENTS’ WRITING SKILL ON PROCEDURE TEXT - Prasetya, Eska Perdana; ., Komarudin (ENGLISH JOURNAL, 2017)
The research is entitled The Use of Cooking Video to Improve Students’ Writing Skill on Procedure Text. Writing is a process of discovering and organizing ideas, putting them on paper and reshaping and revising them. Therefore, the teacher should prepare the media to improve students? writing skill. This paper was aimed to find out the improvement of students? writing skill through cooking video. In this research, the researcher used classroom action research. This research was conducted at SMA Citra Nusa Bogor. The population is 184 students and the researcher took 30 students as a sample. The data were collected using test and observation which were collected during preliminary cycle, cycle-one, and cycle-two. The result of this research shows that cooking video as media is effective in improving the students? writing skill on procedure text. It is indicated by the fact that the average of the test had improved. The average of the test in preliminary cycle was 53, then in cycle-one was 68, and cycle-two was 85. The result of the observation showed there were significant difference between the students? skill, students? participant, and students? interest who were taught by using cooking video and those who were taught before using cooking video. It meant that cooking video could help the students in improving in their skill in writing procedure text. It could also help the teacher to improve the students? participation and interest in writing procedure text.